Jargon language Madura in the community coastal in Pamekasan district (A linguistic study) - Ria Kasanova; Muhammad Darrin Zuhri (Universitas Indraprasta PGRI, 2017)
In a society there is no uniformity of language, although in a monolingual language society (society uses only one language in all life activities). Thus it is clear that the language is not monolithic, not only in one form, but in various forms. Languages that are still within the scope of the same language system (langue) are called language variants. The phenomenon of language other than can be observed as a phenomenon of system or language structure can be observed as a social phenomenon. As a social phenomenon, the use of language in society is influenced by situational factors. In relation to the above matter in this study the researchers further study it through the title of research 'Jargon Madurese Language In Coastal Communities in Pamekasan District (A Linguistic Review)'.